A Short Review on Factors that Impact the Backpressure of exhaust manifold of spark ignition engine - Muhammad Izzat Nor, Ma'arof; Rishan, Murali; Lim, Jin Wei; Mohd Amir Shazwan, Hashim; Girma, Tadesse Chala; Chai, Chuan Ern (INTI International University, 2019)
Exhaust manifold serves as breathing equipment for internal combustion (IC) engine removing combustion products. Backpressure or pressure drop in exhaust manifold is one of the flow characteristic that gives various effect to IC engine. Current methods of estimating the backpressure are through computational fluid dynamic (CFD) analysis and experimental analysis. The effects of backpressure on spark ignition (SI) and compression ignition (CI) engine are usually severe which includes pumping loss, reduced thermal efficiency, increased brake specific fuel consumption (bsfc) and reduced brake power. This paper reviews the Various design parameters that cause backpressure in exhaust manifold such as diameter, shape, length and pipe bend.